Socio-cultural Aspects of Informatization in the Context of the Effective General (Secondary) Education Formation - Zherdev, Denis Vadymovich; Nazarov, Vladimir Lazarevich; Averbukh, Natalya Vladimirovna (KnE Social Sciences, 2021)
This article is devoted to the preparation of an information base for the formation of criteria for assessing the process of general (secondary) education informatization. The situation in education can be considered as unstable, lacking a clear understanding of the social, psychological and technological prospects for the Russian and world communities’ development, which excludes the possibility of correct strategic planning and making correct management decisions. The development source of uncertainty is the very transitional nature of the current situation in ICT — equally in the technological, economic, sociocultural and psychological aspects. The research problematizes the well-established idea of the modern relations of education and ICT, emphasize the lack of empirical data and the bias towards a normative approach in the field of managerial decisions, which in the face of uncertainty leads to the adoption of erroneous decisions (a tactics and strategy contradiction). The research has determined the prospects for a monitoring research system designed to obtain the necessary empirical data in the system, taking into account the change in the technological and sociocultural paradigm over the past decade. Keywords: information society, digitalization of education, efficiency in education, digital divide, resistance to innovation